2019
DOI: 10.3390/nano9070989
|View full text |Cite
|
Sign up to set email alerts
|

Significantly Enhanced Electrical Performances of Eco-Friendly Dielectric Liquids for Harsh Conditions with Fullerene

Abstract: The eco-friendly vegetable liquid is increasingly used because of the growing demand for environmentally friendly dielectric liquid. A vegetable liquid/fullerene nanofluid was fabricated via ultrasonic processing with good dispersion of the fullerene nanoparticles. It was observed that a small amount of fullerene (~100 mg/L) can significantly improve the electrical properties of vegetable insulating liquid (dissipation factor decreased by 20.1%, volume resistivity increased by 23.3%, and Alternating Current (A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 41 publications
0
17
0
Order By: Relevance
“…There is a certain amount of research groups [32,44,50,61,64] that linked the electrical conductivity to nanofluids stability. Nevertheless, in this regard more research is needed to fully describe the phenomenon, even if some comments are present in the open literature.…”
Section: Discussion On Experimental Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a certain amount of research groups [32,44,50,61,64] that linked the electrical conductivity to nanofluids stability. Nevertheless, in this regard more research is needed to fully describe the phenomenon, even if some comments are present in the open literature.…”
Section: Discussion On Experimental Resultsmentioning
confidence: 99%
“…Huang et al [61] used an eco-friendly vegetable liquid (i.e., refined, bleached and deodorized (RDB) oil) as base fluid to prepare nanofluids with fullerene nanoparticles and noticed an augmentation in the electrical properties. For example, the electrical resistivity increased by 23.3% at a concentration of 100 mg/L of fullerene nanoparticles.…”
Section: Literature Overviewmentioning
confidence: 99%
“…It had been stated that smart fluids formed with few particular nanoparticles (NPs) that smart fluids manufactured with some explicit nanoparticles (NPs) may be adapted to the preference of applications [123][124][125][126]. Numerous investigators studied BDS, viscosity, pour point, thermal features and streamer development in nano-based ester liquids [26,127,128]. A substantial enhancement is observed with the suspension of various types of NPs.…”
Section: Nanotechnology and Insulating Fluidsmentioning
confidence: 99%
“…It has been reported that the smart liquids developed with some specific nanoparticles can be customized according to the choice of applications in oil-filled apparatus [1], [24]. Several researchers have investigated dielectric strength, viscosity, pour point, oxidation, dielectric properties, thermal properties, and streamer propagation in nano-based ester fluids [134]- [136]. A significant improvement is noticed with the addition of different nanoparticles.…”
Section: Future Research: Challenges and Prospectsmentioning
confidence: 99%